Anthrax meningoencephalitis secondary to oral infection - Yakupogullari, Y; Kabakus, N; Durukan, M; Kizirgil, A; Bulut, Y; Yilmaz, M (Lippincott Williams & Wilkins, 2006)
[Abstract Not Available]
Keywords: Bacillus-Anthracis; Meningitis